DESAIN INTERIOR KAMAR ANAK USIA 9-12 TAHUN UNTUK PENGAJUAN PROPOSAL DANA PADA PANTI ASUHAN ROHADI KALIWUNGU KENDAL - Setiawati Setiawati (STEKOM PRESS, 2016)
Room space is a place needed to rest comfortably. Room interior design can better support the comfort of a room. In general, children's rooms besides being used for resting are sometimes also used for playing and learning. With a good arrangement, it can add comfort and enthusiasm for children in their activities in their room. In addition, independence can also be taught by caring for and tidying his own room. Practicing independence in children requires habits as learning that can be started by tidying the room and making children trained, controlled and preparation for adulthood. The interior of a child's room can also be adjusted to the child's fondness, hobbies and do not forget to be given education as a balance between playing and children's learning. The use of property and furniture in children's rooms must also be taken into account in terms of safety, comfort and health for children. And to strengthen the sense of kinship between family members it is better not to put television or electronic devices in a child's room, as well as make it easier for parents to monitor children closely and supervise well. Training children to become more independent in a simple way can be started from a small age by caring for goods that enjoy doing well. The choice of furniture to be designated in a child's room must be considered in terms of material safety, the use of chemical paints and shapes that can be adjusted. Thus the child will be more comfortable with a variety of activities, besides that the child can also develop his imagination and creativity. In addition, it is very necessary to support from parents / guardians by giving examples in advance so that children can see immediately and can apply them.